Audit committee attributes and auditor brand name of listed companies in Nigeria - Bala, Hussaini; Amran, Noor Afza; Shaari, Hasnah (Universiti Utara Malaysia, 2019)
This paper examines the effect of audit committee attributes on auditor brand name proxy by the Big 4. The study utilizes 88 listed firms in Nigeria through 440 firm-year observations ranging between the years 2012 to 2016. The data for the study were extracted from the firms’ annual reports and Thompson Reuters DataStream. A panel logistic regression was employed to estimate the model of the study. Consistent with complementary hypothesis the findings demonstrate that audit committee attributes (audit committee independence, audit committee financial accounting experts, audit committee legal expert, female audit committee member and audit committee stock ownership) are positively related to auditor brand name. The findings also support the substitution hypothesis perspectives by revealing an inverse relationship between audit committee meetings, audit committee tenure, audit committee chair and auditor brand name. Our findings offer an initial insight on the effect of audit committee legal expert, and audit committee stock ownership on auditor brand name. Thus, the findings can benefit existing and prospective shareholders who are the direct users of financial reports. This study can also help policy-makers and regulators by allowing them to better recognize the importance of these distinctive audit committee attributes in enhancing the quality of audits, which is one of the most vital elements of improving financial reporting quality.